Tanggungjawab Hukum Partai Politik Terhadap Kader Partai Sebagai Anggota Dewan Perwakilan Rakyat Terkait Tindak Pidana Korupsi - Albariatul Khoir Hasibuan (Jurnal SOMASI (Sosial Humaniora Komunikasi), 2020)
As an organization that is given the authority to nominate candidates for political office, the political party law should have provisions regarding the dismissal of members of political parties in the DPR due to criminal acts of corruption. Against this background, this research examines the seriousness of political parties and their authority in dismissing members of the House of Representatives regarding the crime of corruption, so that the problem in the research that the author is researching is what is the solution that should be taken by political parties in reducing the number of involvement of their cadres in the DPR in criminal acts. corruption? The provision that corporations are considered to have committed a criminal act because people, whether they have a work relationship or other relationship, act for and on behalf of or within the corporate environment as regulated in Article 20 paragraph (2) of Law No. 31/1999 is also found in other statutory regulations. Article 15 paragraph (2) of Emergency Law Number 7 of 1955 concerning Investigation, Prosecution and Economic Crime Justice (hereinafter written as Law No.7 / 1955). Concrete solutions that can be taken by political parties in reducing the involvement of party cadres in criminal acts of corruption are to initiate sanctions for political parties related to criminal acts of corruption and through strengthening the cadre of parties, establishing candidate qualification standards, pushing the law to increase the qualification of DPR members and improving The role of political parties in realizing a clean government.